The Trend of Library Development in Indonesia and the Effects on Literacy Skills in Schools - Listanto, Virgiawan; Firmansyah, Nurhuda (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2022)
This study has the purpose of explaining the trend of library development in Indonesia from 2017-2021, studying the significance, and analysing the effects on the development of literacy skills in schools. This study was designed as a quantitative descriptive, comparison, and correlational analysis. The results of this study indicate that the trend of Library Growth in Indonesia continuously increased except in 2018 due to a regrouping policy for primary schools. Secondly, the library growth in Indonesia has shown a significant difference each year in public and private schools. Although in 2018, there was no significant difference in terms of the average percentage of library growth for schools in both public and private environments, what happened in 2019 and 2020 showed different things. Both public and private school libraries have demonstrated significant differences in the average percentage growth of libraries to schools in 2019 and 2020. Even in 2021, the average accumulation percentage of growth in the number of libraries in public schools is already above 90%, while in private schools, it is still below 90%. Lastly, a significant moderate positive relationship between the national average libraries to school ratio and Alibaca Index/Reading Literacy Score means that a library's presence in schools has moderately influenced students' literacy skills.